Effects of Bni5 Binding on Septin Filament Organization. Issue 24 (4th December 2016) - Booth, Elizabeth A.; Sterling, Sarah M.; Dovala, Dustin; Nogales, Eva; Thorner, Jeremy
Abstract: Septins are a protein family found in all eukaryotes (except higher plants) that have roles in membrane remodeling and formation of diffusion barriers and as a scaffold to recruit other proteins. In budding yeast, proper execution of cytokinesis and cell division requires the formation of a collar of circumferential filaments at the bud neck. These filaments are assembled from apolar septin hetero-octamers. Currently, little is known about the mechanisms that control the arrangement and dynamics of septin structures. In this study, we utilized both Förster resonance energy transfer and electron microscopy to analyze the biophysical properties of the septin-binding protein Bni5 and how its association with septin filaments affects their organization. We found that the interaction of Bni5 with the terminal subunit (Cdc11) at the junctions between adjacent hetero-octamers in paired filaments is highly cooperative. Both the C-terminal end of Bni5 and the C-terminal extension of Cdc11 make important contributions to their interaction. Moreover, this binding may stabilize the dimerization of Bni5, which, in turn, forms cross-filament braces that significantly narrow, and impose much more uniform spacing on, the gap between paired filaments. Graphical Abstract: Highlights: Bni5 localizes to the Saccharomyces cerevisiae bud neck in a septin filament-dependent manner. Bni5 oligomerizes and binds cooperatively to septin Cdc11 and requires its C terminus to do so. Cooperative binding of Bni5 also requires the C terminus of Cdc11. Bni5 decorates paired septin filaments with hetero-octameric periodicity. Bni5 binding restrains and constricts the spacing between paired septin filaments.